2012
DOI: 10.1111/apa.12092
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low birthweight infants: how neonatal intensive care unit teams can reduce postnatal malnutrition and prevent growth retardation

Abstract: Higher parenteral intake and close attention to enteral feeding reduced nutritional deficits and linear growth restriction in infants admitted to a French NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
(47 reference statements)
3
25
0
2
Order By: Relevance
“…In the selected studies achieving near-fetal postnatal growth (table 1), amino acids were supplied immediately after birth at a dose of 1.4 g/kg/d 15 to 3.6 g/kg/d 17. Our approach and suggestions for the introduction and advancement of amino acids are summarised in figure 1.…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…In the selected studies achieving near-fetal postnatal growth (table 1), amino acids were supplied immediately after birth at a dose of 1.4 g/kg/d 15 to 3.6 g/kg/d 17. Our approach and suggestions for the introduction and advancement of amino acids are summarised in figure 1.…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…In another study with the same nutritional targets, Senterre and Rigo [7] also reported no significant decrease in head circumference z-scores between birth and hospital discharge. In addition, several other authors with quite similar nutritional targets also described a similar growth pattern with few PNGR in VLBW infants and no decrease in head circumference z-score between birth and discharge [8,9,10]. …”
Section: Figmentioning
confidence: 71%
“…Nutritional targets in this study need to be considered as insufficient taking into account current recommendations [2,3,4,5] and most recent nutritional studies in VLBW infants [6,7,8,9,10]. Such mistakes in defining adequate nutritional targets have already been made previously and lead to the wrong information that PNGR is inevitable with current recommendations [11].…”
Section: Figmentioning
confidence: 99%
“…Indeed, extra-uterine growth restriction is related to complications associated with prematurity and to deficits in nutrient intakes. Recent studies have suggested that aggressive nutritional support can help to reduce weight and length deficits upon discharge from hospital [1].…”
Section: Introductionmentioning
confidence: 99%